Age-and sex-related changes in selected hematological parameters, lipid peroxidation and erythrocytes osmotic fragility of Turkish Angora cats - Kabakci, Ruhi (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was conducted to investigate the changes in selected hematological parameters, lipid peroxidation and osmotic fragility of erythrocytes in Angora cats depending on the age and gender. For this purpose, the blood samples were collected from 9 young and 14 adult cats which also classified as male (n=12) and female (n=11). Following hematological analysis, samples were washed with PBS by centrifugation and 10% hematocrit suspension was prepared from the erythrocytes pellet for osmotic fragility test. The concentration of malondialdehyde (MDA) was also measured from lysed erythrocyte to determine lipid peroxidation level. Red blood cells (RBCs), hemoglobin, and hematocrit were high in adults while mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration were high in young cats. Erythrocyte MDA level was also higher in adult cats than in young cats. There was no significance in these parameters between male and female cats. Findings of fragility tests were showed that erythrocytes of young and male cats were more susceptible to hypotonic NaCl solutions than those of adult and female cats, respectively. It was concluded that erythrocytes related parameters in Angora cats changed depending on the age rather than gender except stability of RBCs.